Spatial Information Technology Adoption for Developing Data Base of Village Resources - Samsuri; Slamet, Bejo; Zaitunah, Anita; Ahmad, Alfan Gunawan; Razali; Arisandi, Dedi (Talenta Publisher, 2021)
The village has an important role and position in national development because the concentration and other natural resources are in the village. Planning for village development activities must be harmonious and sustainable, so the need for data and information is very important. Lubuk Kertang Village, Pangkalan Brandan District, Langkat Regency is one of the villages with a lot of potentials that can be used as capital in village development. However, the potential data has not been compiled in a database that can be accessed, manipulated, and updated systematically. Therefore, it is necessary to compile a database of village potential to support significant development planning to be directed and achieve goals. The application of spatial technology to build a database on village potential is currently integrated with the internet network. It can be accessed from anywhere and anytime. Exploration of potential data shows that Lubuk Kertang village has the potential for agriculture, fisheries, forestry, small industry, and ecotourism spread across five hamlets. To manage this village potential database, training data administrators in exploring data, inputting data, and updating data is an important factor in managing the village potential database. Village government officials are very interested and can manage their village potential database